"Brave Young Singers": children's poetry-writing and 1930s Australian distance education. Issue 2 (30th September 2014) - Anae, Nicole
Abstract : Purpose: – There has been virtually no explication of poetry-writing pedagogy in historical accounts of Australian distance education during the 1930s. The purpose of this paper is to satisfy this gap in scholarship. Design/methodology/approach: – The paper concerns a particular episode in the cultural history of education; an episode upon which print media of the 1930s sheds a distinctive light. The paper therefore draws extensively on 1930s press reports to: contextualise the key educational debates and prime-movers inspiring verse-writing pedagogy in Australian education, particularly distance education, in order to; concentrate specific attention on the creation and popular reception of Brave Young Singers (1938), the first and only anthology of children's poetry written entirely by students of the correspondence classes of Western Australia. Findings: – Published under the auspices of the Australian Council for Educational Research (ACER) with funds originating from the Carnegie Corporation, two men in particular proved crucial to the development and culmination of Brave Young Singers . As the end result of a longitudinal study conducted by James Albert Miles with the particular support of Frank Tate, the publication attracted acclaim as a research document promoting ACER's success in educational research investigating the "experiment" of poetry-writing instruction through correspondence schooling. Originality/value: – The paper pays due critical attention to a previously overlooked anthology of Australian children's poetry while simultaneously presenting an original account of the emergence and implementation of verse-writing instruction within the Australian correspondence class curriculum of the 1930s.